Effect of Extreme Weather Events on Contaminant Transport From Urban Run-Off to a Fjord System - Breedveld, Gijs D.; Hansen, Mona C.; Hale, Sarah E.; Allan, Ian J.; Hamers, Timo (Frontiers in Environmental Science, 2021)
Urbanization has resulted in increased contaminant run-off in densely populated areas. Climate change is expected to result in a higher frequency of extreme weather events including torrential rainfall and storms. The contaminant levels of polycyclic aromatic hydrocarbons (PAH), chlorinated paraffins (CPF) and selected metals, in a small urban river was monitored during snow-melting and rainfall events to quantify the contribution to the contamination load of receiving waters of the inner Oslo fjord, Norway. Suspended particulate matter (SPM) was characterized with respect to levels of contaminants as well as toxic response using a battery of bioassays. The contaminant flux from the river to the fjord was quantified and assessed relative to historic sediment data. Historic data for near-shore sediment samples from the fjord were used to document urban input. The results show a clear episodic response in contaminant load emitted from the river to the fjord. The main historic input to the fjord was found to be PAH from pyrogenic sources like coal and wood burning as well as traffic. A significant reduction in the level of PAH was observed since the 1980s. The measured flux of CPF is consistent with on-going societal use despite a ban on the use of short chain CPF imposed in Norway from 2002.